Local proliferation of macrophages contributes to obesity-associated adipose tissue inflammation - Amano, Shinya U. (2013)
Adipose tissue (AT) of obese mice and humans accumulates immune cells, which secrete cytokines that can promote insulin resistance. AT macrophages (ATMs) are thought to originate from bone marrow-derived monocytes, which infiltrate the tissue from the circulation. Here we show that a major fraction of macrophages unexpectedly undergo cell division locally within AT, as detected by Ki67 expression and 5-ethynyl-2′-deoxyuridine incorporation. Macrophages within the visceral AT (VAT), but not those in other tissues, including liver and spleen, displayed increased proliferation in obesity. Importantly, depletion of blood monocytes had no impact on ATM content, while their proliferation in situ continued. Treatment with monocyte chemotactic protein 1 (MCP-1) induced macrophage cell division in AT explants, while MCP-1 deficiency in vivo decreased ATM proliferation. These results reveal that proliferation in situ driven by MCP-1 is an important process by which macrophages accumulate in the VAT in obesity, in addition to blood monocyte recruitment.